Efficacy of different parts of Tridax procumbens as a potential biolarvicide against Aedes aegypti and Aedes albopictus - Dinesh Rajendran,; Shaida Fariza Sulaiman,; Wan Fatma Zuharah, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The epidemic of dengue and Zika outbreak transmitted by Aedes mosquitoes has been a global issue and plenty of preventive measurements are being used. Due to environmental awareness, people are opting on bioinsecticide. The objective of this research is to study on the effectiveness of different parts of Tridax procumbens plant on Aedes aegypti and Aedes albopictus larvae. Tridax procumbens are endemic plants in Malaysia. Using WHO standard larval bioassay, third instar larvae of Ae. aegypti and Ae. albopictus were exposed to different concentrations, ranging between 250ppm-2500ppm for three different parts of T. procumbens plant extracts obtained from Soxhlet extraction. Larval mortality was observed after 24-hour exposure. The highest toxicity for Ae. aegypti was recorded by T. procumbens stem extract with the LC50 of 799.78ppm. The pairwise comparison showed, the highest mean mortality value for stem did not show any significant difference with leaves; however, it did show a significant difference with flowers when tested on Ae. aegypti (P<0.05). Meanwhile for Ae. albopictus, the highest toxicity recorded with the LC50 of 583.63ppm was by the T. procumbens flower extract. The mean mortality value for flower showed significant differences from other plant parts when tested on Ae. albopictus (P<0.05). This indicates that T. procumbens is effective in killing both Ae. aegypti and Ae. albopictus.